My magnetic shape book :early learners (Dorling Kindersley New York, 2001)
My Magnetic Shape Book by DK is an interactive children's book designed to teach basic shapes through fun, magnetic pieces. It helps young readers develop shape recognition and fine motor skills in a playful, hands-on way.